A water-soluble octahedral molybdenum cluster complex as a potential agent for X-ray induced photodynamic therapy - Kirakci, Kaplan; Pozmogova, Tatiana N; Protasevich, Andrey Y; Vavilov, Georgy D; Stass, Dmitri V; Shestopalov, Michael A; Lang, Kamil (Biomaterials science, 2021)
X-ray-induced photodynamic therapy (X-PDT) has recently evolved into a suitable modality to fight cancer. This technique, which exploits radiosensitizers producing reactive oxygen species, allows for a reduction of the radiation dose needed to eradicate cancer in the frame of the radiotherapy treatment of deep tumors. The use of transition metal complexes able to directly produce singlet oxygen, O2(1Δg), upon X-ray irradiation constitutes a promising route towards the optimization of the radiosensitizer's architecture. In our endeavour to conceive pertinent agents for X-PDT, we designed an octahedral molybdenum cluster complex (Mo6) with iodine inner ligands, and carboxylated apical ligands bearing ethylene oxide organic functions. The sodium salt of this complex is highly soluble in aqueous media and displays red luminescence which is efficiently quenched by oxygen to produce O2(1Δg) in a high quantum yield. Furthermore, due to its high radiodensity, the complex exhibits radioluminescence in aqueous media, with the same spectral features as for photoluminescence, indicating the production of O2(1Δg) upon X-ray irradiation. The uptake of the complex by Hep-2 and MRC-5 cells is negligible during the first hours of incubation, then considerably increases in connection with the hydrolysis of the apical ligands. The complex exhibits low toxicity in vitro and induces a radiotoxic effect, noticeable against cancerous Hep-2 cells but negligible against normal MRC-5 cells, at X-ray doses that do not affect cell viability otherwise. The first evaluation of in vivo toxicity of an Mo6 complex on a mouse model evidences a moderate and delayed toxic effect on kidneys, with an intravenous LD50 value of 390 ± 30 mg kg-1, possibly connected with hydrolysis-induced aggregation of the complex. Overall, this complex displays attractive features as a singlet oxygen radiosensitizer for X-PDT, highlighting the potential of transition metal cluster complexes towards this modality.
Keywords: fotosenzibilizující látky; myši; rentgenové záření; Singlet Oxygen; Molybdenum; fotochemoterapie; zvířata; Mice; Water; singletový kyslík; molybden; Photochemotherapy; X-Rays; Photosensitizing Agents; voda; Animals